2020
DOI: 10.1038/s41598-020-76318-5
|View full text |Cite|
|
Sign up to set email alerts
|

Modifying the thickness, pore size, and composition of diatom frustule in Craspedostauros sp. with Al3+ ions

Abstract: Diatoms are unicellular photosynthetic algae that produce a silica exoskeleton (frustule) which exposes a highly ordered nano to micro scale morphology. In recent years there has been a growing interest in modifying diatom frustules for technological applications. This is achieved by adding non-essential metals to the growth medium of diatoms which in turn modifies morphology, composition, and resulting properties of the frustule. Here, we investigate the frustule formation in diatom Pinnularia sp., including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
0
12
0
1
Order By: Relevance
“…Therefore, SEM by employing FIB‐SSV and TEM by employing ET can be used profitably in the elucidation of the ultrastructure of healthy and pathological bone. Last but not least, techniques involving electron microscopes not only provide structural information of the bone tissue, but can also provide useful structural insights into other biological or synthetic materials such as biological exoskeletons (Rivera et al, 2020 ; Soleimani et al, 2020 ; Sun & Bhushan, 2012 ; Yao et al, 2010 ), biomimetic materials (Dede Eren et al, 2020 ; Mohammadi, Sesilja Aranko, Paul Landowski, Wagermaier, & Linder, 2019 ; Wegst, Bai, Saiz, Tomsia, & Ritchie, 2015 ), and implant materials (Linder et al, 1983 ; Mendonça, Mendonça, Aragão, & Cooper, 2008 ; Thorfve, Palmquist, & Grandfield, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SEM by employing FIB‐SSV and TEM by employing ET can be used profitably in the elucidation of the ultrastructure of healthy and pathological bone. Last but not least, techniques involving electron microscopes not only provide structural information of the bone tissue, but can also provide useful structural insights into other biological or synthetic materials such as biological exoskeletons (Rivera et al, 2020 ; Soleimani et al, 2020 ; Sun & Bhushan, 2012 ; Yao et al, 2010 ), biomimetic materials (Dede Eren et al, 2020 ; Mohammadi, Sesilja Aranko, Paul Landowski, Wagermaier, & Linder, 2019 ; Wegst, Bai, Saiz, Tomsia, & Ritchie, 2015 ), and implant materials (Linder et al, 1983 ; Mendonça, Mendonça, Aragão, & Cooper, 2008 ; Thorfve, Palmquist, & Grandfield, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are about 20,000 species of diatoms with pores arranged in a beautiful and rigid walled nanoarchitecture [ 52–54 ]. These pores range in size from 3 to 50 nm in diameter [ 55 ]. Besides being found in all types of water bodies they are photosynthetic, convert atmospheric CO 2 to carbohydrates, thus forming different biomolecules like proteins, lipids, carotenoids, etc.…”
Section: Diatoms Silica Shells As Robust Nanomaterials To Treat Heavy Metals In Waste Watermentioning
confidence: 99%
“…At the same time, the role of this element in biomineralization has not been fully studied, nor has its effect on the structure of the formed BSi. Several studies reported that Al has been uptaken by the cell when forming the frustule [88]. Aluminum is included into the frustule during silicification, which suggests the structural incorporation of Al inside the silica framework synthesized by the organism.…”
Section: Aluminummentioning
confidence: 99%
“…The incorporation of Al into the diatom frustule modifies its properties and affects the solubility of BSi [89,90]. Most notably, Al incorporation into the frustules of several diatom species leads to a significantly enhanced hydrolysis resistance and longer lifetime of frustules compared to Al-free ones [88,90,91].…”
Section: Aluminummentioning
confidence: 99%